2015
DOI: 10.2197/ipsjtcva.7.121
|View full text |Cite
|
Sign up to set email alerts
|

Upper Body Pose Estimation for Team Sports Videos Using a Poselet-Regressor of Spine Pose and Body Orientation Classifiers Conditioned by the Spine Angle Prior

Abstract: Abstract:We propose a per-frame upper body pose estimation method for sports players captured in low-resolution team sports videos. Using the head-center-aligned upper body region appearance in each frame from the head tracker, our framework estimates (1) 2D spine pose, composed of the head center and the pelvis center locations, and (2) the orientation of the upper body in each frame. Our framework is composed of three steps. In the first step, the head region of the subject player is tracked with a standard … Show more

Help me understand this report

Search citation statements

Order By: Relevance

Paper Sections

Select...
1
1
1

Citation Types

0
3
0

Year Published

2016
2016
2022
2022

Publication Types

Select...
4
2

Relationship

0
6

Authors

Journals

citations
Cited by 6 publications
(3 citation statements)
references
References 57 publications
(160 reference statements)
0
3
0
Order By: Relevance
“…The presented results of both papers show how the head-and upper-body-pose is leveraged for individual players, resulting in 3D visualizations that could be then studied by coaches. Later, the same authors [33] extended their previous work by training a poselet-regressor that produces an accurate estimation of the spine pose. By introducing priors based on the spine angle, several body classifiers are trained, which result in a coarse orientation of the upper body; note that, once the head region of each player is detected, the contribution of the presented regressor is to estimate the relative pelvis location for each target.…”
Section: A Head-pose-gaze Estimation In Sportsmentioning
confidence: 99%
“…The presented results of both papers show how the head-and upper-body-pose is leveraged for individual players, resulting in 3D visualizations that could be then studied by coaches. Later, the same authors [33] extended their previous work by training a poselet-regressor that produces an accurate estimation of the spine pose. By introducing priors based on the spine angle, several body classifiers are trained, which result in a coarse orientation of the upper body; note that, once the head region of each player is detected, the contribution of the presented regressor is to estimate the relative pelvis location for each target.…”
Section: A Head-pose-gaze Estimation In Sportsmentioning
confidence: 99%
“…Hayasahi et al [16] proposed a CNN model visual imagery analyzer to recognize the upper body pose features and use the head and pelvis to get the spine orientation and estimate body orientation to estimate the random decision of human movement. Jian et al [40] developed an AI coach camera system to collect the 'great' pose of athlete in the spatialtemporal sequence.…”
Section: Postural Assessment Using Markerless-based Approachmentioning
confidence: 99%
“…As presented at five workshops on computer vision in sports held at CVPR or ICCV since 2013, many vision based approaches 18) were proposed to analyze ball possession 19)20) , ball/player trajectory 21) , player identification 22) , pose estimation for sports action recognition 4) and activity recognition in sports applications 3) . The papers in the workshops also reported that a deep learning approach like 23) was particularly valuable.…”
Section: Sports Analysismentioning
confidence: 99%